EU Cohesion at sub-Regional Level. The Case of the sub-Regions of Warmińsko-Mazurskie Voivodship - Kamil Kotliński (Barometr Regionalny)
Warmińsko-Mazurskie Voivodship is one of the poorest EU regions. The region is internally diverse at the sub-regional level. The aim of the study is to assess the effectiveness of cohesion policy in the sub-regions (NUTS 3 ) of the Warmińsko-Mazurskie Voivodship: Ełcki, Elbląski, and Olsztyński. The basis of assessment that was adopted was the change of position relative to all EU-sub-regions. Changes of economy structure are studied using the changes of the shares of sectors — NACE Rev. 2 in creating the Gross Value Added. The source of data is Eurostat. The results are ambiguous. Although some indicators (employment and GDP per capita) have improved, sigma convergence does not occur and the positions of those sub-regions do not show any significant changes, only Olsztyński sub-region noted small improvement in the ranking. Very small progress in the ranking means that the pace of catching up is too slow. Despite this, effects of membership in the European Union for employment and growth is positively assessed.